Afro-Sweden : becoming Black in a color-blind country - Skinner, Ryan Thomas (University of Minnesota Press, 2022)
"The first scholarly monograph in English to focus on the African and Black diaspora in Sweden, Afro-Sweden emphasizes the voices, experiences, practices, knowledge, and ideas of these communities. Its interdisciplinary approach to understanding diasporic communities is essential to contemporary conversations around such issues as the status and identity of racialized populations in Europe and the international impact of Black Lives Matter"--